7T Spin-echo BOLD fMRI enhances spatial specificity in the human motor cortex during finger movement tasks - SoHyun Han; Dongho Kim; Seulgi Eun; HyungJoon Cho; Seong-Gi Kim (NeuroImage)
The human primary motor cortex (M1) follows a well-established somatotopic organization, yet finer-scale representations, such as mirrored finger maps, have remained difficult to resolve non-invasively. To investigate movement representations in an action-based framework rather than a strictly somatotopic layout, we conducted both conventional gradient-echo (GE) and highly specific spin-echo (SE) BOLD fMRI at 7 T with 1 mm isotropic resolution. Subjects performed 1-Hz visually-instructed thumb–index finger or thumb–ring finger opposition tasks, and their finger movements were recorded using an MR-compatible data glove to verify proper task performance. In each subject, the activated M1 region spanning multiple slices was subdivided into ten columns along a medial-to-lateral axis. Finger dominance (index vs. ring) was determined within each column. In GE-BOLD fMRI, two distinct tasks exhibited similar activation patterns across columns, reflecting its limited ability to resolve columnar activation differences due to contamination from draining vein effects. In contrast, SE-BOLD fMRI revealed alternating task dominance across columns, demonstrating higher spatial specificity compared to GE-BOLD. By integrating SE-BOLD fMRI, but not GE-BOLD, with behavioral data, we present a more accurate mesoscopic mapping of motor activity in individual subjects. These findings provide non-invasive evidence of fine-grained motor organization, demonstrating the utility of SE-BOLD contrast for mapping mesoscopic representations.